Diet-related determinants of childhood obesity in urban settings: a comparison between Shanghai and New York. Issue 4 (April 2015) - Leung, M.M.; Fu, H.; Agaronov, A.; Freudenberg, N.
Abstract Over the past three decades, both Shanghai and New York City (NYC), have experienced dramatic rises in childhood obesity rates. Given the role that obesity plays in the aetiology of chronic diseases such as diabetes and heart disease, the elevated rates are a major concern. Despite differences in governance systems and cultures, Shanghai and NYC have experienced rapid industrialization, a growing population and a rise in income inequality. The prevalence of childhood obesity in Shanghai and NYC is greater than their respective national rate. However, the trajectory and development of this epidemic has differed between the cities. The distribution of obesity by race and ethnicity, socio-economic status, sex, and age differs markedly between the two cities. To reduce prevalence and inequities within this complex epidemic requires an understanding of the dynamic changes in living conditions among social groups in each city and the behaviours that are influenced by such changes. By comparing changes in the influences on dietary behaviours, such as food distribution, pricing, gender values, and media and marketing, this highlights opportunities for Shanghai, NYC, and other world cities with high or rising rates of childhood obesity to inform future program and policy initiatives. It reiterates the importance of a comprehensive and multilevel approach that includes action at the individual, family, community, municipal, national, and global levels.